“Making Generation Y Stay”: The Mediating Role of Organizational Commitment - Sellya Putri; Bertina Sjabadhyni; Martina Dwi Mustika (Psikohumaniora: Jurnal Penelitian Psikologi, 2018)
Job turnover in Generation Y has become a common phenomenon in industry in large cities. They tend to believe that it is not difficult to leave their jobs and not important to immediately settle in an organization. The study aimed to understand the mediating role of organizational commitment (OC) between perceived organizational support (POS) and turnover intention (TO). A purposive sampling technique was used in this study with 284 generation Y employees living in large cities (19-37 years old) as participants. There were three questionnaires used in this study namely Turnover Intention Scale, Organizational Commitment Scale and Survey of Perceived Organizational Support. The investigation discovered that POS positively affected OC and negatively TO. Employing mediation analysis showed that OC was a significant mediator from the relationship of POS and TO. The findings of this research provide organizations with information about how to effectively manage and retain Generation Y employees through POS and OC.